EFEKTIVITAS ENKAPSULASI ENZIM PROTEASE DENGAN BEAD HIDROGEL BERBAHAN ALGINAT-KITOSAN - Christian Joseph Tanuwidjaja; Eko Adi Prasetyanto (Bahasa Indonesia, 2022)
Introduction: The addition of the protease enzyme from an external source can increase protein absorption in the human digestive system. Protease enzyme is formulated by encapsulated inside alginate-chitosan hydrogel beads to deny immediate proteolysis reaction with the protein consumed and maintain the encapsulated enzyme in a temperature range acidity. This research aims to know the encapsulation effectivity of protease enzyme with alginate-chitosan hydrogel beads. Methods: Experiments were conducted to encapsulate protease enzyme with ionotropic gelation method using alginate and chitosan. Encapsulation yield, bead size, encapsulated enzyme activity, release rate, and stability were analyzed from the hydrogel beads that were obtained. The data is then analyzed using analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). Results: From four variants of hydrogel beads that were obtained, this research shows that the volume addition of alginate solution in the encapsulation material will increase the value of encapsulation yield (EY), bead size, and release rate of the encapsulated protease enzyme. Therefore, the volume addition of chitosan solution will increase the value of encapsulation efficiency (EE). Hydrogel beads incubation at 6°C for 24 days maintain 75,55% of encapsulated enzyme activity. Conclusion: Protease enzyme can be formulated with protein by being encapsulated with alginate-chitosan hydrogel beads. Key Words: alginate, chitosan, protease enzyme encapsulation